Can multiple forms of undernutrition among children and women be tackled efficiently? A case of shared determinants (P11-124-19) - Avula, Rasmi; Nguyen, Phuong Hong; Pramanik, Priyanjana; Tran, Lan Mai; Ruel, Marie T.; Menon, Purnima (Oxford University Press, 2019)
Globally, it is recognized that multiple forms of undernutrition exist. Yet, little evidence exists on co-existence of multiple forms of undernutrition or on the potential shared determinants of these manifestations. Therefore, using data from India, we aimed to: 1) estimate the co-occurrence of undernutrition among children (stunting and anemia) and women (underweight and anemia); and 2) identify their shared determinants.